Smartphone Technology for Reporting Errors in Error Management Contexts - R. León, Federico (2025)
Whereas error prevention in organizations recurs to diverse ways of ensuring that worker behavior complies with norms, rules, and procedures and to elimination of the precursors of error (ineffective layout, inadequate task demands, weak training), error management accepts error as unavoidable and emphasizes its positive administration. The error management sequence starts with the detection of error and follows with its reporting, identification of causes, correction, and institutionalization of the correction. However, error management lags behind error prevention in use of tools of the digitalization/automation era. We developed an application for worker’s use of his/her smartphone to report errors ―SOLUCIONA― in error management. Before disseminating it, workers of six plants of a Peruvian gas bottling company received training to improve worker empowerment in error reporting as part of company strategy. Then, workers of three plants were trained to use SOLUCIONA whereas workers of three other plants maintained use of pencil and paper. The experimental design took into account the latitude and altitude of the plants’ locations in the Peruvian territory. We obtained pretest and posttest measurements which included an adaptation of Rybowiak et al. (1999)’s Error Orientation Questionnaire. Experimental group workers ―exposed to SOLUCIONA― quintupled the frequency of error reporting compared to control workers and experimental managers significantly increased their frequency of solutions. The technological intervention did not impair worker empowerment; rather, it brought advantages in subjective competence and learning from errors. We conclude that smartphone technology improves error management without adverse effects.